Pengembangan Desa Wisata Berbasis Edukasi Sampah dan Bahasa Jepang di Kabupaten Bogor - Mustaqim, Naufal; Taufiqurrahman, Nabil; Alesandra, Junita; Shaleha, Chandra Kirana; Tsani, Mohammad Farkhan; Santoso, Sarah Azzahra; Alaydrus, Abdillah Hasan; Lee, Carmel Avrilia Tonny; Insani, Listriasa Rizka Karima; Farhansyah, Farhansyah; Syafitri, Dinda Nur; Tallulembang, Nadya Hadasa; Nanoka, Takahashi; Yume, Matsubara; Mikoto, Yamashita (Jurnal Pusat Inovasi Masyarakat, 2025)
This service activity aims to increase students' knowledge of waste, introduce students to multicultural concepts, and develop tourism in Benteng Village through cleanliness and Japanese. The main target of this program is 5th grade students of SDN Benteng 01. The method of activity implementation includes interactive teaching by native speakers, pre-test, post-test, observation, hands-on practice, and literature review. Japanese language education delivered directly by native speakers is able to increase students' courage, critical thinking, motivation to learn, and increase global insight. The introduction of Japanese is seen as an innovative step to support the development of new tourism potential in Benteng Village, along with the foreign culture tourism that has been developed in the village. In addition, waste education was conducted by providing material on the types of waste and how to process them, which ended with fun activities such as singing songs about waste and making tanabata. The pre-test and post-test results were analyzed using the paired sample t-test parametric test and showed a significant increase in students' knowledge related to waste, while the results of the tanabata in the form of hanging pots were displayed in front of the school. This activity has great potential in tourism development in Benteng Village. With an understanding of waste and Japanese language from an early age, it can make students aware of the importance of protecting the environment and motivated to study harder. This program has succeeded in developing tourism in Benteng Village indirectly, which may be felt in the coming years.